Dziennik z Grasse Galiny Kuzniecowej — autoportret pisarki - Brzykcy, Jolanta (Przegląd Rusycystyczny, 2017)
Grasse Diary (Грасский дневник, 1967), the most famous work by Galina Kuznetsova, for years has been treated mostly as the book about Ivan Bunin. It contains her account of fifteen years spent with Bunin in Grasse and Paris, wherefore it has been attracted particular interest of Bunin’s researchers. Bunin is the central figure of Grasse Diary, yet Kuznetsova, according to Lejeune’s „autobiographical pact”, remains the author, the narrator of her story and character who is being talked about. Discrete entries include her experiences, thoughts, feelings, comment on current events. Kuznetsova creates the self-portrait, presents a deeply subjective vision of the world. Some equal strategies can be found in her narration: an observer strategy, participant strategy and introspection strategy. The aim of this paper is to analyse them and to interpretate Kuznetsova’s image given in her daily entries.